ENT530 : D' fresh Food Industries / Siti Mastura Mohd Nor, Jumailah Mohd Ali and Muhammad Fikri Abd Manaf - Mohd Nor, Siti Mastura; Mohd Ali, Jumailah; Abd Manaf, Muhammad Fikri (2017)
It is important for a company to market their products. A company needs to investigate their vision and mission to the marketplace. However there are pros and cons on their business strategy. Hence, the study and understanding of customer needs is very important before a product is released. The purpose of the present study was to determine what is the problem occurs in the company for market their product in the local market. How many problems do they face and how to help solve their problems. Based on interviews and verbal surveys most of them request that flavors be diversified as well as promotions that need to be held from time to time to introduce Bumiputera products that are increasingly popular in the local market.